„Innobyty” – kres antropocentryzmu, początek człowieczeństwa? - Krajewska, Anna (Przestrzenie Teorii, 2023)
Editorial on the concept of other beings (non-human beings) towards the end of anthropocentrism, a new dimension of humanity, devoted to aesthetics related to the creation of ontoepistemology.